Work-related musculoskeletal disorders and its association with physical fitness among physiotherapy students attending public universities in Malaysia/ Fatim Tahirah Mirza, Awatif Syazani Roslan and Ain Saiful Bahri - Mirza, Fatim Tahirah; Roslan, Awatif Syazani; Saiful Bahri, Ain (Faculty of Health Sciences, Universiti Teknologi MARA, 2019)
Physical fitness plays a key role in minimizing work-related musculoskeletal disorders (WRMSDs) among physiotherapists. A cross-sectional study was undertaken to determine the prevalence of WRMSDs and their associated factors among physiotherapy students in public universities in Malaysia. A self-administered questionnaire (Standardized Nordic Questionnaire) was distributed and physical fitness level was assessed on 114 undergraduate physiotherapy students from the only three public universities in Malaysia offering Physiotherapy program. Physical fitness assessments consisted of body composition, muscle flexibility, muscle strength and cardiorespiratory endurance tests. The overall prevalence of WRMSDs among physiotherapy students was 82% with more female reported having WRMSDs when compared to males students (84% vs. 73%, p <0.000). The lower back was reported as the body area most affected by WRMSDs within the past 12-months and 7 days (31% and 24%, respectively) followed by neck (16% and 10%, respectively) and shoulder (11% and 7%, respectively). Significant differences were observed between the proportion of students who had undergone clinical placement between 10-15, 16-20, and 21-25 weeks (χ2 = 8.80 p = 0.003) on WRMSDs. However, no significant differences were observed on the prevalence of WRMSDs across BMI and level of physical fitness. In summary, the prevalence of WRMSDs among physiotherapy students in Malaysia is high and physical fitness are not associated with WRMSD.